Post-translational dysregulation of glucose uptake during exhaustive cycling exercise in vastus lateralis muscle of healthy homozygous carriers of the ACE deletion allele - Flück, Martin; Vaughan, David; Rittweger, Jörn; Giraud, Marie-Noëlle (Frontiers in Physiology, 2022)
Homozygous carriers of the deletion allele in the gene for angiotensin-converting enzyme (ACE-DD) demonstrate an elevated risk to develop inactivity-related type II diabetes and show an overshoot of blood glucose concentration with enduring exercise compared to insertion allele carriers. We hypothesized that ACE-DD genotypes exhibit a perturbed activity of signaling processes governing capillary-dependent glucose uptake in vastus lateralis muscle during exhaustive cycling exercise, which is associated with the aerobic fitness state. 27 healthy, male white Caucasian subjects (26.8 ± 1.1 years; BMI 23.6 +/- 0.6 kg m-2) were characterized for their aerobic fitness based on a threshold of 50 mL O2 min-1 kg-1 and the ACE-I/D genotype. Subjects completed a session of exhaustive one-legged exercise in the fasted state under concomitant measurement of cardiorespiratory function. Capillary blood and biopsies were collected before, and ½ and 8 hrs after exercise to quantify glucose and lipid metabolism-related compounds (lipoproteins, total cholesterol, ketones) in blood, the phosphorylation of 45 signaling proteins, muscle glycogen and capillaries. Effects of aerobic fitness, ACE-I/D genotype, and exercise were assessed with analysis of variance (ANOVA) under the hypothesis of a dominant effect of the insertion allele. Exertion with one-legged exercise manifested in a reduction of glycogen concentration ½ hour after exercise (-0.046 mg glycogen mg-1 protein). Blood glucose concentration rose immediately after exercise in association with the ACE-I/D genotype (ACE-DD: +26%, ACE-ID/II: +6%) and independent of the fitness state (p=0.452). Variability in total cholesterol was associated with exercise and fitness. In fit subjects, the phosphorylation levels of glucose uptake-regulating kinases [AKT-pT308 (+156%), SRC-pY419, p38a-pT180/T182, HCK-pY411], as well as cytokine/angiotensin 1-7 signaling factors [(STAT5A-pY694, STAT5B-pY699, FYN-pY420, EGFR-pY1086] were higher in ACE I-allele carriers than ACE-DD genotypes after exercise. Conversely, the AKT-S473 phosphorylation level (+117%) and angiotensin 2’s blood concentration (+191%) were higher in ACE-DD genotypes. AKT-S473 phosphorylation levels post-exercise correlated to anatomical parameters of muscle performance and metabolic parameters (p<0.05 and │r│>0.70). The observations identify reciprocal alterations of S473 and T308 phosphorylation of AKT as gatekeeper of a post-translational dysregulation of transcapillary glucose uptake in ACE-DD genotypes which may be targeted in personalized approaches to mitigate type II diabetes.